ENERGY DISSIPATION CHARACTERISTICS OF NON-LINEAR NORMAL VIBRATION CONTACT INTERFACE - ZHANG MingSong; PANG Dan; WANG Hong; HUANG Tao; MING Ming (Jixie qiangdu)
The energy dissipation characteristics of the non-linear normal vibration contact system of the interface have important theoretical and engineering significance for describing the dynamic mechanism of the interface.Based on Hertz contact theory, the dynamic model of nonlinear normal vibration contact of damping joint interface is established, and the dynamic response of damped free vibration and simple harmonic forced vibration and the calculation method of vibration contact energy dissipation are proposed; the non-linearity is established The dynamic equation of the normal vibration contact system, the energy dissipation rate and cumulative energy dissipation rate of damped free vibration, and the input energy and damping loss energy of simple harmonic forced vibration are calculated; the nonlinear normal vibration contact interface is studied The relationship between energy dissipation characteristics and energy transfer provides a theoretical basis for describing the dynamics of the vibrating contact interface.